Potential Fit between Geotechnical Tasks and Mobile Computing Technologies - Shehzad, Aamer; Zaidi Abd Rozan, Mohd (International Journal of Engineering and Technology, 2018)
Trend of rapid pace in earthworks has forced geotechnical laboratories to increase their productivity and performance at organizational as well as at individual level. Though geotechnical work involves numerous mobile work processes but the true potential of rapidly growing mobile computing technologies (MCT) has not yet been effectively exploited mainly due to lack of realization of a potential match between features of this specific technological paradigm and major task requirements.Â  To fill this gap, this study investigated and characterized salient task characteristics and features of MCT. Based on the theory of task-technology fit (TTF), an initial conceptual model is proposed which reflects hypothesized relationships for finding a fit between task and technology and consequently assessing its impact on performance of geotechnical field workers. This paper contributes to the knowledge pool of information system through development of an adapted TTF model in geotechnical mobile work context. Lastly, future research plan of using quantitative methodology for finding empirical support of this conceptual model is presented.Â Â